Exploring The Multifaceted Nature of Organisational Culture: Key Dimensions and Their Interrelationships - Reshma, P.; Kumar, S. Makesh; Madhavan, S. (Journal of Neonatal Surgery, 2026)
Organisational culture is a multifaceted construct comprising of interwoven dimensions that shape employee experience and organisational effectiveness. This research delves into the complex nature of organisational culture, exploring its key dimensions and their intricate interrelationships, with a specific focus on Work Engagement, Workplace Flexibility, Performance, Aid & Assistance, Professional Growth, and Internal Communication. The study examines how these dimensions interact and influence each other to create a holistic cultural landscape. This research employs a mixed-methods approach, combining a comprehensive literature review with empirical data gathered through questionnaire from employees of IT industries in India. The findings reveal significant interdependencies between the chosen dimensions, demonstrating how a focus on one area can have cascading effects on others. For instance, organisations that promote Workplace Flexibility may also see increased Work Engagement and improved Performance. The study concludes by offering practical recommendations for leaders and managers seeking to cultivate a positive and productive organisational culture, emphasizing the importance of understanding and strategically managing the interplay between these key dimensions. It also identifies potential avenues for future research, particularly regarding the dynamic evolution of organisational culture and the impact of external factors on these interrelationships.